Conservação de espécies nativas em um assentamento rural do município de Apodi-RN: impactos socioambientais e econômicos e o uso da biotecnologia como alternativa promissora - Bezerra, Rafaela Maria de França (2013)
The Caatinga biome has a high diversity of potential and their conservation constitutes one of the greatest challenges of Brazilian science. The sustainable management of the Caatinga emerges as an alternative that through the formation of systems agrossilvipastoris, enables the use of forest resources sustainably, ensuring their conservation, regeneration and recovery. In RN this technique has been developed mainly in settlements of Agrarian Reform, such as P. A. Moaci Lucena, and their impacts go beyond the environmental aspect and reverberate socially and economically on the quality of life of family farmers. Despite the efficiency of the Sustainable Management of the Caatinga in the conservation of native species, many forests species of this biome faces serious problems of propagation and for this reason have become vulnerable to extinction, as is the case of Mimosa caesalpiniifolia Benth . Thus , it is evident the need to use sustainable alternatives to overcome the difficulties of propagation of this species and enable their replacement in areas where their existence is threatened. The Plant Biotechnology is considered as a promising alternative in this sense, considering that by micropropagation enables the large-scale production of seedlings with high health genetics status. This work has the following objectives: evaluate the perception of family farmers of P. A. Moaci Lucena in relation to social, environmental and economic impacts of the Sustainable Management of the Caatinga and check the conditions of germination and in vitro propagation of Mimosa caesalpiniifolia Benth that enabling the production of seedlings of this specie on a large scale. To achieve the first objective, semi-structured interviews showed that in the perception of farmers PA Moaci Lucena, the Sustainable Management of the Caatinga was responsible for generating many social, environmental and economic impacts that affected directly in the improvement in the quality of life of the families of the Settlement Project Moaci Lucena. Have to achieve the second objective, were investigated the influence of different substrates and concentrations of growth regulator BAP in the germination and shoot induction in vitro of Mimosa caesalpiniifolia Benth. The vermiculite was presented as the most suitable substrate for germination of this species, because it provided a more rapid germination, higher growth rates and higher dry matter accumulation. Regarding micropropagation, the concentration of 17.76 μmol/L of BAP presented a more responsive in relation to multiplication rate and the number of shoots in M. caesalpiniifolia, thus constituting the most suitable concentration for the in vitro propagation of this specie